1998
DOI: 10.1109/27.725141
|View full text |Cite
|
Sign up to set email alerts
|

High rep rate high performance plasma focus as a powerful radiation source

Abstract: Basic operational characteristics of the plasma focus are considered from design perspectives to develop powerful radiation sources. Using these ideas we have developed two compact plasma focus (CPF) devices operating in neon with high performance and high repetition rate capacity for use as an intense soft X-ray (SXR) source for microelectronics lithography. The NX1 is a four-module system with a peak current of 320 kA when the capacitor bank (7.8 F 2 4) is charged to 14 kV. It produces 100 J of SXR per shot … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
57
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(58 citation statements)
references
References 12 publications
1
57
0
Order By: Relevance
“…[3][4][5][6][7][8][9]. A most comprehensive review of the state of the art can be found in Bernard et al 10 The approach followed in the present work is to use the electron beam generated backward by the Plasma Focus device to generate xrays upon conversion of the beam onto a metal target.…”
mentioning
confidence: 99%
“…[3][4][5][6][7][8][9]. A most comprehensive review of the state of the art can be found in Bernard et al 10 The approach followed in the present work is to use the electron beam generated backward by the Plasma Focus device to generate xrays upon conversion of the beam onto a metal target.…”
mentioning
confidence: 99%
“…6,7,10,11,[14][15][16] An improved five-phase code crucially incorporating small disturbance speed, 17 and radiation coupling with dynamics, assisted further projects, 8,[18][19][20][21][22][23] and was published in the internet in 2000 ͑Ref. The basic model was described in 1984 ͑Ref.…”
mentioning
confidence: 99%
“…The basic model was described in 1984 ͑Ref. It has been used in machines including UNU/ICTP PFF, 10,11,15,16,21 NX2, [18][19][20] and NX1, 18 and has been adapted to the Filippovtype DENA. 6,7,10,11,[14][15][16] An improved five-phase code crucially incorporating small disturbance speed, 17 and radiation coupling with dynamics, assisted further projects, 8,[18][19][20][21][22][23] and was published in the internet in 2000 ͑Ref.…”
mentioning
confidence: 99%
“…16) and used in the design and interpretation of experiments. [17][18][19] An improved 5-phase code 2 incorporating finite small disturbance speed, 20 radiation and radiation-coupled dynamics was used, [21][22][23] and was web-published 24 in 2000. Plasma self-absorption was included 24 in 2007.…”
Section: The Lee Model Codementioning
confidence: 99%